2020
DOI: 10.1007/s41999-020-00420-0
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions, attitudes and training needs of primary healthcare professionals in identifying and managing frailty: a qualitative study

Abstract: Purpose Although frailty can be delayed or prevented by appropriate interventions, these are often not available in countries lacking formal education and infrastructure in geriatrics. The aim of this study was to: (a) explore ideas, perceptions and attitudes of primary health care (PHC) professionals towards frailty in a country where geriatrics is not recognised as a specialty; (b) explore PHC professionals’ training needs in frailty; and (c) define components of a frailty educational programme in PHC. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 27 publications
(28 reference statements)
5
37
1
Order By: Relevance
“…PHC professionals neither considered frailty as a fatality nor its screening pointless or beyond their duties. This perception implies the unmet need of PHC professionals for education and training in dealing with frailty, which was also pointed out in the qualitative part of the present study [22] and in another qualitative study from Italy [29].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…PHC professionals neither considered frailty as a fatality nor its screening pointless or beyond their duties. This perception implies the unmet need of PHC professionals for education and training in dealing with frailty, which was also pointed out in the qualitative part of the present study [22] and in another qualitative study from Italy [29].…”
Section: Discussionsupporting
confidence: 76%
“…The focus groups aimed at investigating the status of clinical practice, attitudes and educational needs of participants regarding frailty; results of which can be found in another publication [22].…”
Section: Methodsmentioning
confidence: 99%
“…A research team from one such country, Greece, therefore sought to explore the possibility of developing a primary care frailty service. 1 They found that primary care clinicians considered the main barriers for the identification and management of frailty to be associated with the structure of the healthcare system, including duration of appointments, a focus on prescribing, a lack of allied health professionals, and a lack of training opportunities. The authors offer various solutions as to how primary care clinicians can be trained to improve frailty care but notably, do not include the apparently more obvious solution of developing geriatric medicine as a dedicated specialty training pathway.…”
Section: Frailty Gestational Diabetes Shared Cancer Care and Positive Healthmentioning
confidence: 99%
“…Consequently, basic principles of GM, essential for dealing with older people, are commonly unknown. Recent research has demonstrated the gap in GM education as the main barrier to providing person-centered care for older people with frailty in the community [ 4 ]; nevertheless, it has been observed that physicians and nurses are motivated and receptive to training in geriatric skills with a direct clinical application [ 5 ]. Moreover, even in countries with developed GM systems, there is often a vague understanding amongst GPs and specialists of what GM is and what geriatricians do [ 3 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%